The effect of fartlek and shuttle run training on 60 meter sprint running speed - Arsadi, Ihsan; Endrawan, I Bagus; Fikri, Aprizal; muslimin, Muslimin (Citius : Jurnal Pendidikan Jasmani, Olahraga, dan Kesehatan, 2025)
Running speed is an important component of students' physical ability, particularly in athletics. Research into appropriate exercise methods to increase running speed, such as fartlek and shuttle runs, is important. This study aimed to determine the effect of fartlek and shuttle run training on the 60-metre sprint speed of students at SMP Negeri 02 Belitang, using an experimental approach with a two-group pretest-posttest design. The sample consisted of 15 SMP Negeri 02 Belitang students. A 60-metre sprint test was used to measure changes in performance before and after the exercise treatment. Paired t-test results showed that both fartlek and shuttle run exercises significantly increased running speed (p-value <0.05). The shuttle run group experienced an average time decrease of 0.8 seconds (t = 5.50, df = 6, p = 0.002), demonstrating greater performance improvement than the fartlek group. In conclusion, both fartlek and shuttle run training were effective in increasing the 60-metre sprint speed of junior high school students. The shuttle run had a greater effect on performance improvement than fartlek. For future studies, it would be advisable to include variables such as gender, age, and initial fitness level to enable a more comprehensive analysis.